Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Integration by parts



$$x^2e^{-3x}dx =-\frac13e^{-3x}\left(x^2+\frac23x+\frac29\right)+c$$

I have


Can anyone please help me?

share|cite|improve this question
I am a bit confused as to your question. Do you wish to see how these integrals are solved using integration by parts? – Kris Williams May 12 '13 at 2:17
Please check to be sure that I interpreted everything correctly. Would you like me to add the missing integral signs? – Brian M. Scott May 12 '13 at 2:17
up vote 1 down vote accepted

First one:

Recall that $d(\arctan(x)) = \dfrac{dx}{1+x^2}$. $$\int x \arctan(x) dx = \underbrace{\int \arctan(x) d\left(\dfrac{x^2}2 \right)}_{\displaystyle \int v du} = \overbrace{\dfrac{x^2 \arctan(x)}2}^{\displaystyle uv} - \underbrace{\int \dfrac{x^2}{2(1+x^2)}dx}_{\displaystyle \int u dv}$$ Now $$\int \dfrac{x^2}{2(1+x^2)}dx = \int \dfrac{1+x^2-1}{2(1+x^2)}dx = \int \dfrac{dx}2 - \int \dfrac{dx}{2(1+x^2)} = \dfrac{x}2 - \dfrac{\arctan(x)}2$$ Hence, we get that $$\int x \arctan(x) dx = \dfrac{x^2 \arctan(x)}2 - \dfrac{x}2 + \dfrac{\arctan(x)}2 + c = \dfrac{(1+x^2) \arctan(x)}2 - \dfrac{x}2 + c$$

Second one:

$$\int x^2 e^{-3x} dx = \underbrace{\int x^2 d \left(\dfrac{e^{-3x}}{-3}\right)}_{\displaystyle \int v du} = \overbrace{\dfrac{e^{-3x}}{-3} x^2}^{\displaystyle uv} - \underbrace{\int \dfrac{e^{-3x}}{-3} (2x) dx}_{\displaystyle \int u dv} = \dfrac{e^{-3x}}{-3} x^2 + \dfrac23 \int xe^{-3x} dx$$ Now let us do integration by parts again to evaluate $\displaystyle \int xe^{-3x} dx$. $$\int xe^{-3x} dx = \underbrace{\int x d \left(\dfrac{e^{-3x}}{-3}\right)}_{\displaystyle \int v du} = \overbrace{x \dfrac{e^{-3x}}{-3}}^{\displaystyle uv} - \underbrace{\int \dfrac{e^{-3x}}{-3} dx}_{\displaystyle \int u dv} = -\dfrac{x e^{-3x}}3 - \dfrac{e^{-3x}}{27}$$ Putting this back, we get that $$\int x^2 e^{-3x} dx = -\dfrac13 e^{-3x}x^2 - \dfrac29 e^{-3x}x - \dfrac2{27} e^{-3x} + c = - \dfrac{e^{-3x}}3 \left(x^2 + \dfrac{2x}3 + \dfrac2{27}\right) + c$$

share|cite|improve this answer
Generally, if you're gonna put two $$ you don't need to use \dfrac. – Asaf Karagila May 12 '13 at 2:24
@AsafKaragila Ok. But why not? Is there any difference when we view it? – user17762 May 12 '13 at 2:26
The d in the \dfrac is short for \displaystyle, so whenever you write \dfrac{}{} it is equivalent to writing {\displaystyle\frac{}{}}. Since in $$ mode you already find yourself in a \displaystyle environment, there's no need to use \dfrac again. Similarly if you have explicitly stated \displaystyle in the code prior to the \frac's. – Asaf Karagila May 12 '13 at 2:28

Hold onto your hat: For the integral $$\int x^2e^{-3x}dx$$ we will let $u= x^2$ and $dv=e^{-3x}dx$. Thus, $du = 2x dx$ and $v = \dfrac{e^{-3x}}{-3}$.

Thus we have $$\int x^2e^{-3x}dx = x^2 \frac{e^{-3x}}{-3} - \int 2x \dfrac{e^{-3x}}{-3} dx.$$

For the latter integral above, we simplify and factor out the constants so that we have $$\dfrac{2}{-3} \int x e^{-3x}dx.$$

Now we let $u= x$, $dv = e^{-3x}dx$. Then $du=dx, v=\dfrac{e^{-3x}}{-3}$. Hence we have $$\dfrac{2}{-3} \int x e^{-3x}dx = \dfrac{2}{3} \left( x \dfrac{e^{-3x}}{-3} - \int \dfrac{e^{-3x}}{-3} dx\right) = \dfrac{2}{-3} \left(x \dfrac{e^{-3x}}{-3} + \dfrac{e^{-3x}}{-9} \right).$$

Putting this all together,

$$\int x^2e^{-3x}dx = e^{-3x} \left(\frac{1}{-3} x^2 - \frac{2}{9}x -\frac{2}{27} \right) + C$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.